Preservation of Endangered Indigenous Knowledge - Twinoburyo, Dianah Kacunguzi (Qualitative and Quantitative Methods in Libraries, 2019)
Preservation of indigenous knowledge (IK) is an issue of concern among nations today. IK is invaluable and serves as a gateway to understanding our past and should be preserved to remind us of who we are and where we have come from so as not to lose our cultural identity. However, IK is facing the possibility of total extinction in many countries including Uganda. The danger is that once lost, IK is lost forever. This study sought to closely examine ways in which endangered IK can be preserved to prevent possible extinction and ensure long-term use by future generations. Specifically, the role of community libraries was assessed to extend our understanding of how they engage with varied indigenous groups in Uganda to facilitate ongoing practices and preserve their knowledge for future generations. Data was obtained through unstructured interviews with nineteen librarians from all registered community libraries in Kampala District.